Diet-induced reconstruction of mucosal microbiota associated with alterations of epithelium lectin expression and regulation in the maintenance of rumen homeostasis - Hong Shen (Nature Portfolio, 2017)
Abstract It is unknown whether lectins of the rumen epithelium contribute to the recognition of mucosal microbes and activation of tolerogenic cytokines in ruminant animals. We applied an integrated method of RNA-seq and 16S rRNA gene sequencing to investigate alterations of epithelial lectin expression and regulation with a diet-induced reconstruction of the mucosal microbiota in the goat rumen. Our results showed that the diversity and richness of the rumen mucosal microbiota were promoted by the dietary concentrate. Meantime, in the rumen epithelium, five lectin genes, namely, sialic acid-binding Ig-like lectin 14 (LOC102180073), C-type lectin domain family 4, member E (CLEC4E), C-type lectin domain family 7, member A (CLEC7A), C-type lectin domain family 16, member A (CLEC16A), and lectin, mannose-binding 2 (LMAN2), were indicated to promote the expression of 8 tolerogenic cytokines, transforming growth factor beta 1 (TGFB1) and 4 enzyme genes involved in retinoic acid biosynthesis via 6 signaling pathways. Analysis of the combined data showed that 9 microbial genera (Clostridium_IV, Desulfobulbus, Eubacterium, Ochrobactrum, Propionibacterium, Pseudomonas, Slackia, Staphylococcus and Subdivision5_genera_IS) were highly related to the expression of functional lectins. These findings provide new insights into the interactions between the rumen epithelium and mucosal microbiota in the maintenance of rumen homeostasis.